Hubungan Bahaya Paparan Asap Rokok dengan Kejadian TB Paru Pada Anak di RSUD DR. H. Abdul Moeloek Provinsi Lampung - Ida Rahmatika; Linawati Novikasari; Rika Yulendasari (Malahayati Nursing Journal, 2025)
ABSTRACT Bandar Lampung City is the city/district that has the highest prevalence of pediatric TB cases in Lampung Province, namely 790 cases. In 2022, the coverage of TB case detection in children will be 59.4% and this coverage is higher than in 2021, namely 35.1%. Based on medical record data that researchers conducted at RSUD Dr. H. Abdul Moeloek, Lampung Province, it is known that the incidence of pulmonary TB in children in 2023 from January to September is 61 cases. It is known that there is a relationship between the dangers of exposure to cigarette smoke and the incidence of pulmonary TB in children. This type of research is quantitative research with an Analytical Survey research design with a Case Control approach. The total sample was 94 respondents using Purposive Sampling Technique. And analysis uses the Chi Square test. Analysis of the frequency distribution of exposure to cigarette smoke found 52 (55.3%) in the category not exposed to cigarette smoke. And as many as 42 (44.7%) were exposed to cigarette smoke. Analysis of the frequency distribution of history of pulmonary TB: 47 (50.0%) were in the category of not having pulmonary TB and 47 (50.0%) had pulmonary TB. Chi Square analysis test on the relationship between exposure to cigarette smoke and the incidence of pulmonary TB in children, obtained a significant p-value of 0.000 ( 0.05). This shows that there is a relationship between the dangers of exposure to cigarette smoke and the incidence of pulmonary TB in children. It is hoped that parents will keep their children away from cigarette smoke so that they are not exposed to cigarette smoke which will result in pulmonary TB in children. Keywords: Cigarette Smoke, Pulmonary TB, Children  ABSTRAK Kota Bandar Lampung adalah Kota/Kabupaten yang memiliki prevalensi dengan penemuan kasus TB anak tertinggi di Provinsi Lampung yaitu sebesar 790 kasus. Pada tahun 2022, cakupan penemuan kasus TB pada anak sebesar 59,4% dan cakupan ini lebih tinggi dibandingkan tahun 2021 yaitu sebesar 35,1%. Berdasarkan data rekam medik yang peneliti lakukan di RSUD Dr. H. Abdul Moeloek Provinsi Lampung, diketahui bahwa angka kejadian TB paru pada anak di tahun 2023 mulai periode bulan Januari sampai dengan September sebanyak 61 kasus. Diketahui hubungan antara bahaya paparan asap rokok dengan kejadian TB paru pada anak. Jenis penelitian ini adalah penelitian kuantitatif dengan desain penelitian Survei Analitik pendekatan Case Control. Jumlah sampel 94 responden dengan Teknik Purposive Sampling. Dan analisis menggunakan uji Chi Square. Analisis distribusi frekuensi paparan asap rokok terdapat 52 (55,3%) dalam kategori tidak terpapar asap rokok. Dan sebanyak 42 (44,7%) mengalami terpapar asap rokok. Analisis distribusi frekuensi riwayat TB paru 47 (50,0%) dalam kategori tidak terkena TB paru dan sebanyak 47 (50,0%) mengalami TB paru. Uji analisis Chi Square pada hubungan antara paparan asap rokok dengan kejadian TB paru pada anak, didapatkan nilai signifikan p-value 0,000 ( 0,05). Hal ini menunjukkan bahwa ada hubungan antara bahaya paparan asap rokok dengan kejadian TB paru pada anak. Diharapkan orang tua menjauhkan anak dari asap rokok agar tidak terpapar asap rokok yang akan mengakibatkan kejadian TB paru pada anak. Kata Kunci: Asap Rokok, TB Paru, Anak